Developing Arabic Language Content on TikTok and Instagram: Educational Opportunities for the Digital Native Generation - Ahmadi Ahmadi (STIQ Amuntai, 2025)
The rapid growth of social media has positioned it as an influential alternative learning space, particularly for the digital native generation that actively engages with visual and interactive content. This study seeks to examine the educational potential of Arabic language learning through short-form videos disseminated via popular platforms such as TikTok and Instagram. Employing a descriptive qualitative method, data were gathered through systematic content analysis of Arabic learning videos, in-depth interviews with digital educational content creators, and focused group discussions with students of Arabic Language Education (PBA). The findings indicate that short video formats, enhanced with appealing visual elements, interactive features, and communicative language styles, significantly capture learners’ attention while simultaneously fostering motivation and sustained engagement. In addition, these platforms provide a more informal and dynamic interaction space between educators and learners, enabling flexible knowledge exchange within the digital ecosystem. The study underscores the strategic urgency of developing micro-content-based approaches in order to make Arabic language education more adaptive, innovative, and responsive to the learning patterns of Generation Z.